The effect of carbamazepine, which increases oestrogen destruction, on the endometriotic implants; an experimental rat model. (4th July 2022) - Bulbul, Mehmet; Nacar, Mehmet Can; Aydin Turk, Bilge; Karacor, Talip; Onderci, Muhittin; Parlar, Ali; Kirici, Pınar; Ucar, Cihat
Abstract: We planned this experimental study to investigate the effect of carbamazepine (CMZ) on the endometriotic implants. Rats were randomised into four groups after endometriosis surgery. Drinking water was given to the sham group, 0.2 mg/kg oestradiol valerate (EV) to the EV group, 100 mg/kg/day CMZ to the CMZ group, and 0.2 mg/kg EV and 100 mg/kg/day CMZ to the EV-CMZ group. The endometrium of the rats using CMZ stained more intensely with cytochrome P450-3A4 (CYP3A4) enzyme. No endometrial hyperplasia was found in these rats. Endometriotic implants weight was found to be higher in these rats. There was no difference between the groups in terms of staining of the endometriotic implants with CYP3A4 enzyme. Endometriotic implants were less stained with the CYP3A4 enzyme than the endometrium. According to our results, CMZ does not increase the destruction of oestrogen in the endometriotic implants, unlike the endometrium. It may even cause the lesion to enlarge. Impact statement: What is already known on this subject? Endometriosis is an oestrogen-dependent, progressive disease. Carbamazepine (CMZ) is known to increase oestrogen degradation by activating the cytochrome P450-3A4 (CYP3A4) enzyme. CMZ can be used in the treatment of endometriosis because it increases oestrogen breakdown in tissues. What do the results of this study add? CMZ can protect the endometrium against hyperplasia by increasing the amount of CYP3A4 enzyme in the endometrium. This effect could not be demonstrated in the endometriotic implants. The presence of CYP3A4 enzyme less in the endometriotic implants than in the endometrium may explain this situation. In addition, the fact that CMZ does not increase the enzyme in the endometriotic implants may contribute to this situation. What are the implications of these findings for clinical practice and/or further research? CMZ may not be a suitable alternative in the treatment of endometriosis. However, it may protect against endometrial hyperplasia. Clinical studies are needed for this effect.